(untitled) (International Journal of Food and Nutritional Sciences, 2022)
In India there are more than 14,000 medicinal plants species used as Ayurveda and Siddha ,Unani and Homeopathy.It is estimated that there are about 960 species of medicinal plants on the market.In the present study we have carried out a survey on medicinal plants in Maharashtra rural areas of Sangamner city. The plants were used by local areas people nearby village were surveyed ,collected and identified.In all the cases of medicinal plants used parts were determined.All together 26 species we are studied there use an important role in medicine.